A Case of Extranodal Marginal Zone Lymphoma of the Lung: Case Report - Bektas, Sevda Sert; BİRCAN, Sema; Bircan, Ahmet; BİRCAN, HACI AHMET; Yavuz, Gulcan; Gunes, Sedat; Sirmali, Mehmet; Alanoglu, Guchan (My University, 2012)
Lymphomas originating from lung constitute less than 1% of all non-Hodgkin lymphomas. Most of them are MALT (mucosa-associated lymphoid tissue) lymphomas originating from bronchial mucosa-related lymphoid tissue. Extranodal MALT lymphomas are slowly progressing lymphomas involving mucosa-related lymphoid tissue (MALT), they remain as a localized mass for a long time and bone marrow and peripheral lymph node involvements are seen very rarely. Patient survival is long and the response rate to treatment is high. In this paper, we present a 56-year-old male patient in whom an incidental mass lesion was detected in the right lung on chest radiography obtained when he was being followed up for brain edema. Widespread lymphoid cell infiltration was seen in the initial bronchoscopic tissue biopsy, and he was diagnosed as MALT-type extranodal marginal zone lymphoma after examination of the wedge resection material. The case was discussed in the lightof radiological, clinical and pathological findings.